Heat Transport and Water Permeability during Cracking of the Landfill Compacted Clay Cover - Haijun Lu; Jianjun Liu; Yuan Li; Yiqie Dong (Journal of Chemistry)
The heat-moisture transport through the compacted clay was observed in laboratory. The hydraulic conductivity of cracked clay under wetting-drying cycles was also investigated. At the early phase of heating, the temperature of soil columns rose fast and moisture decreased dramatically; after this phase, the temperature rose at a lower speed and moisture loss stabilized gradually. The moisture content of compacted clay at 25 cm depth decayed to 0. The crack intensity factor (CIF) of compacted clay was 0.043 and 0.097; the crack depth was about 6.5 cm and 8.2 cm at 50°C and 60°C, respectively. The hydraulic conductivity of compacted clay was within 8.3 × 10−7 to 1.5 × 10−5 cm/s after four wetting-drying cycles. This value was 2~3 orders of magnitude higher than that of uncracked clay.